FORMAL AND INFORMAL INSURANCE MARKET INSTITUTIONS (INNOVATIVE ECONOMY, 2021)
Nikiforov P.O., Нladchuk O.M., Kucherivska S.S. FORMAL AND INFORMAL INSURANCE MARKET INSTITUTIONSPurpose. The purpose of the article is to defining the nature, types, and role of formal and informal insurance market institutions.Methodology of research. The methodological basis of the work has become a systematic approach to the study of the formation and functioning of formal and informal insurance market institutions; as well as a dialectical method of cognition and grouping to determine the types of formal and informal institutions that have formed and ensure the development of insurance relationships. Methods of induction and deduction have been used to generalize the essence and role of insurance market institutions under the provisions of economic theory and insurance business. The differences between formal and informal insurance market institutions have been established by a comparative method. To make theoretical generalizations, to form conclusions from the study, an abstract reasoning method has been used.Findings. The article presents the results of empirical analysis of formal and informal institutions, under the influence of which the insurance market has been formed and is currently functioning. Formal insurance market institutions are clearly defined, regulated by public protection mechanisms, and mandatory for all economic entities involved in the insurance process. Informal insurance market institutions are unwritten and undocumented norms and rules that shape the behaviour of economic entities of the insurance market regarding the creation, purchase and sale, and consumption of insurance services. Both formal and informal insurance market institutions should be divided into basic and specific ones, taking into account the peculiarities of the insurance market and the specifics of insurance relationships.Originality. Given the peculiarities of the insurance business, formal and informal insurance market institutions are clearly distinguished, with their subsequent division into basic and specific ones.Practical value. The results of the study can serve as a basis for further research in this area and will be useful for insurers, supervisory authorities, and other participants in the insurance market in terms of improving the quality of insurance services, identifying areas of the insurance market, and efficiency of its participants, which will increase confidence in the insurance market.Key words: institution, formal institution, informal institution, insurance market, basic insurance market institution, specific insurance market institution.
Keywords: Key words; institution; formal institution; informal institution; insurance market; basic insurance market institution; specific insurance market institution.